Development of Edmodo Media with Learning Videos to Improve Understanding and Mathematical Resilience on Derivative Material - Farman Farman; Fitriyani Hali; Karman Karman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The low participation of students in online interactive learning was due to the inappropriate use of media and online learning designs. In these conditions, it is necessary to use media that can facilitate the online learning process optimally. This study aimed to compile and obtain video-assisted Edmodo media on valid, practical, and effective derivative materials for class XI students. Video-assisted Edmodo media was chosen to improve students' mathematical understanding and resilience. This media development was developed using the ADDIE model, which consisted of several steps: analysis, design, development, implementation, and evaluation. This research and development subjects were senior high school students of class XI in Kendari. The data collection instrument in this study consisted of a validation sheet, a questionnaire, and a test. The validation results of material and media experts showed that the design of the developed learning material video was in very valid criteria. The analysis of student response data showed that the average score of students' responses to the learning process, learning videos, and student worksheets was positive. The analysis of mathematical understanding and resilience showed that the average of students' understanding ability was in the high category and the students' mathematical reliability was in the high category too. Thus, the Edmodo video media for learning mathematics for functional derivatives met the criteria (valid, practical, and effective) in improving students' mathematical understanding and resilience.